English language internship – translation project (2021)
At the University of Córdoba, the internationalization processes of the different programs are becoming more visible every day. Teachers and students see the need to promote international academic events with expert guests in other languages ​​recognized in the different areas and knowledge of academic programs. The need for publications in specialized magazines abroad has also increased. Due to this growth, the support of students and teachers of the degree program in foreign-English languages ​​of the faculty of education in supporting translation processes to teachers interested in publishing their research projects, and performing interpretations at events, is even more noticeable, we aim to generate national and international visibility for the academic program, the Department of Foreign Languages, the Faculty of Education and the University of Córdoba with regard to the offer of translation and interpretation services to the educational community and the region, also being an opportunity for The English Degree program responds to the need for publication in international contexts where English, French and Portuguese are required.